Влияние масштаба на электрофизические параметры компонентов микроэлектромеханических систем - Невлюдов, И. Ш.; Палагин, В. А.; Богдан, Ю. И.; Томанова, С. М. (НТУ "ХПИ", 2014)
Теории подобия и размерностей физических величин (ТП и РФВ) содержат основные принципы для оценки изменения свойств МЭМС при уменьшении линейных размеров. Различные активные силы меняются по разным законам, эти силы перечислены в статье. ТП и РФВ могут использоваться для анализа и оценки изменения характеристик МЭМС. В статье показаны некоторые основные тенденции микроминиатюризации.

Similitude and dimension physical quantities theories (TS and DPQ) are basic principles for estimation of changing properties MEMS with decreasing linear scale. Different active forces changes with distinguish laws and these forces are enumerated. In the article surface tension force, electrostatic interactions and electromagnetic interactions are analized. TS and DPQ can be used for analysis and estimation changing characteristics of microelectromechanical systems. These theories help to choose rational functioning principle of MEMS. Also using TS and DPQ allows to estimate the correctness of results, which were obtained with other methods. In the report some principle tendencies of miniaturization are shown.
Influence of linear dimensions change on electrical parameters of microelectromechanical system’s components
Keywords: теория подобия; микросистемная техника; эффекты масштабирования; миниатюризация; теория аналогий; Similitude theory; microsystem machinery; scaling; miniaturization